Play and its pedagogical potential in an preschool institutions - Slunjski, Edita (Array, 2014)
The role of playing in young children's educational process is priceless. It represents the child's zone of proximal development and a possible transition into a higher stage of his/her cognitive and social development, and should be regarded as an integral part of the educational process in the institutions for early education. This implies providing proper conditions for playing and developing playing experiences, which includes creating a safe place and a positive environment for playing, offering "open" materials suitable for different stages of a child's development, providing enough uninterrupted playtime, showing an interest for children's activities and achievements, strengthening the children's cooperation, providing enough time for self-organization of the activities and allowing enough time to carefully listen and observe the children playing. Types of games and their complexity and educational value can be perceived from various perspectives, i.e. observed in terms of various theoretical approaches. This paper analyses playing from two framework perspectives - cognitive and social, and addresses the conditions in early education institutions needed for its uninterrupted activity and its pedagogic potential.